Piezoelectric elastomer material and preparation method and application thereof
By using materials composed of piezoelectric molecular crystals and degradable polymer elastic matrix in the field of biomedical science, the problem that existing piezoelectric materials are difficult to meet multiple requirements at the same time is solved, and the comprehensive effect of high voltage electrical performance, good biocompatibility and degradability is achieved.
Patent Information
- Application Number
- CN202510324441.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
Existing inorganic piezoelectric materials, piezoelectric polymers and composite piezoelectric elastomers are difficult to meet the multiple requirements of materials in the biomedical field at the same time, including high-voltage electrical properties, good biocompatibility, degradability and stable mechanical properties.
A material consisting of piezoelectric molecular crystals and a degradable polymer elastic matrix is used, where the piezoelectric molecular crystals are connected to the three-dimensional network structure of the polymer elastic matrix through hydrogen bonds to form a piezoelectric elastomeric material with high voltage electrical coefficients and good elastic properties.
It has achieved widespread application of materials in the field of biomedical science, combining high voltage electrical coefficient, excellent biocompatibility, safe degradability and good mechanical properties, and improved the fatigue resistance and biosafety of the device.
Smart Images

Figure CN119842213A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of piezoelectric materials, and in particular to a piezoelectric elastomer material and a preparation method and application thereof. Background Art
[0002] Piezoelectric materials are a type of functional material with special properties. They can generate electric fields under mechanical stress or produce mechanical deformation under the action of electric fields. Therefore, they are widely used in the fields of sensors, actuators and other smart materials. In the field of biomedical engineering, piezoelectric materials can produce effects similar to endogenous electric fields in biological tissues, and can interact with biological systems at the cellular level, so that piezoelectric materials can transmit electrical stimulation to biological cells, thereby affecting and regulating many basic physiological processes. Therefore, by applying piezoelectric materials to biological systems, artificial regulation of life processes can be achieved, thereby achieving the purpose of auxiliary treatment.
[0003] The application of piezoelectric materials in the biomedical field places strict requirements on their performance. Piezoelectric materials need to be able to withstand complex mechanical stresses and deformations while maintaining their piezoelectric properties. This means that piezoelectric materials not only need to have sufficient strength and hardness, but also need to have good elasticity and flexibility to adapt to various movements and deformations of organisms. In addition, piezoelectric materials also need to have good biocompatibility to avoid adverse reactions or damage to organisms. In order to avoid secondary damage to organisms due to the need to remove piezoelectric materials from organisms, piezoelectric materials must also be safely degradable or excreted from the body through the biological metabolic system.
[0004] However, existing inorganic piezoelectric materials, piezoelectric polymers and composite piezoelectric elastomers often find it difficult to meet these requirements at the same time. Although inorganic piezoelectric materials have excellent piezoelectric properties, their biocompatibility and degradability are poor, and they are usually hard and lack flexibility. While piezoelectric polymers such as polyvinylidene fluoride (PVDF) have good flexibility and biocompatibility, their piezoelectricity and degradability still need to be improved. The solid filler particles in the composite piezoelectric elastomer cannot be effectively dispersed in the polymer phase, and because the piezoelectric phase is randomly oriented in the polymer, further polarization treatment is required to achieve the ideal electrical properties. This results in uneven and unstable elastic and mechanical properties of the composite elastomer, which weakens its actual composite effect.
[0005] Therefore, how to make piezoelectric elastomer materials have appropriate strength and hardness, good elasticity and flexibility, excellent biocompatibility, safe degradability or be excreted from the body through the biological metabolic system is a problem that needs to be solved urgently. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a piezoelectric elastomer material and a preparation method and application thereof. The piezoelectric elastomer material has suitable strength and hardness, good elasticity and flexibility, a high piezoelectric coefficient, excellent biocompatibility, and safe degradability or can be excreted from the body through the biological metabolic system, thereby solving the biosafety issues encountered in the application of piezoelectric materials in the biomedical field.
[0007] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a piezoelectric elastomer material, comprising piezoelectric molecular crystals and a polymer elastic matrix, wherein the polymer elastic matrix forms an elastic skeleton of a three-dimensional network structure, the piezoelectric molecular crystals are connected to the three-dimensional network structure of the polymer elastic matrix through hydrogen bonds and filled in the pores of the elastic skeleton, the components of the piezoelectric molecular crystals include hexafluoropentanediol or dodecafluorononanediol, the components of the polymer elastic matrix are degradable elastic polymers, the degradable elastic polymers include degradable water-based polyurethane polymers or degradable polyester polymers, and the mass ratio of the piezoelectric molecular crystals to the polymer elastic matrix is (0.2-3):1.
[0008] Further preferably, the mass ratio of the piezoelectric molecular crystal to the polymer elastic matrix is (1-2):1.
[0009] In a possible implementation, the soft segment of the degradable waterborne polyurethane polymer includes at least one of polyether and polyester.
[0010] In a possible implementation, the degradable polyester polymer includes at least one of a random copolyester of ethylene glycol-cyclohexanedimethanol-succinic acid and a random copolyester of ethylene glycol-cyclohexanedimethanol-furandicarboxylic acid.
[0011] In a possible implementation manner, the piezoelectric coefficient of the piezoelectric elastic material is greater than 1 pC / N.
[0012] In a possible implementation manner, the elastic modulus of the piezoelectric elastomer material is 0.5-50 Mpa.
[0013] More preferably, the mass ratio of the piezoelectric molecular crystal to the polymer elastic matrix is (1-1.5):1.
[0014] Furthermore, the piezoelectric coefficient of the piezoelectric elastomer material is greater than 18 pC / N.
[0015] Furthermore, the elastic modulus of the piezoelectric elastomer material is 2.5-7 Mpa.
[0016] In a possible implementation, the length of the piezoelectric molecular crystal is 0.2-80 μm.
[0017] In a second aspect, the present invention further provides a method for preparing the above-mentioned piezoelectric elastomer material, comprising the following steps: S1. A solution of piezoelectric molecules is blended with a solution of a degradable elastic polymer to form a mixed solution, wherein the piezoelectric molecules include hexafluoropentanediol or dodecafluorononanediol, and the degradable elastic polymer includes a degradable waterborne polyurethane polymer or a degradable polyester polymer; in the mixed solution, the mass ratio of the piezoelectric molecules to the degradable elastic polymer is (0.2-3):1; S2. The mixed solution in step S1 is subjected to solvent volatilization, crystal growth and drying treatments to make the degradable elastic polymer form a polymer elastic matrix, and at the same time, piezoelectric molecular crystals grow spontaneously inside the polymer elastic matrix to obtain a piezoelectric elastomer material.
[0018] In a possible implementation manner, the solvents of the solution of the piezoelectric molecules and the solution of the degradable elastic polymer in step S1 include at least one of water, ethanol, chloroform and ethyl acetate.
[0019] In a possible implementation, the mass volume ratio of the piezoelectric molecules to the solvent in the piezoelectric molecule solution in step S1 is 10-600 mg / mL.
[0020] In a possible implementation manner, in the degradable elastic polymer solution in step S1, the mass volume ratio of the degradable elastic polymer to the solvent is 100-600 mg / mL.
[0021] In a possible implementation manner, the process of preparing the solution of the piezoelectric molecules in step S1 is that the piezoelectric molecules are dissolved in the solvent, and the dissolution temperature is 10-60° C. and the time is 5-60 min.
[0022] In a possible implementation, the preparation process of the degradable elastic polymer solution in step S1 is that the degradable elastic polymer is dissolved in the solvent, and the dissolution temperature is 10-60° C. and the time is greater than 1 min.
[0023] In a possible implementation, the blending temperature in step S1 is 10-40°C.
[0024] In a possible implementation manner, the blending time in step S1 is 10-60 min.
[0025] In a possible implementation manner, the temperature at which the solvent is volatilized in step S2 is 30-40°C.
[0026] In a possible implementation manner, the time for the solvent to evaporate in step S2 is 6-12 hours.
[0027] In a possible implementation manner, the temperature of the crystal growth in step S2 is 10-60°C.
[0028] In a possible implementation manner, the crystal growth time in step S2 is 2-6 h.
[0029] In a possible implementation manner, the drying temperature in step S2 is 20-60° C. and the drying time is 12-36 h.
[0030] In a third aspect, the present invention also provides applications of the above-mentioned piezoelectric elastomer material in the fields of biomedicine, wearable devices or piezoelectric generators.
[0031] Based on the common knowledge in this field, the above-mentioned implementation modes can be combined arbitrarily.
[0032] The reagents and raw materials used in the present invention are commercially available.
[0033] The positive and progressive effects of the present invention are: The piezoelectric elastomer material provided by the present invention not only has suitable strength and hardness, good elasticity and flexibility, high piezoelectric coefficient, excellent biocompatibility, safe degradability or can be excreted from the body through the biological metabolic system, but also has an unconventional piezoelectric coefficient change trend. The piezoelectric coefficient of conventional piezoelectric elastomer materials decreases with the increase of strain, while the piezoelectric coefficient of the piezoelectric elastomer material in the present invention continues to increase with the increase of strain, which not only ensures the piezoelectric stability of the piezoelectric elastomer material under strain conditions, but also increases the fatigue resistance of the device in the long-term strain process. The piezoelectric coefficient of the piezoelectric elastomer material provided by the present invention can be as high as 26.25 pC / N, and the shape of the output piezoelectric response peak of 4000 continuous impact cycles remains basically unchanged. The preparation method of the piezoelectric elastomer material provided by the present invention is simple and safe, and is very suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 These are X-ray diffraction test spectra of hexafluoropentanediol powder, the aqueous polyurethane film prepared in Comparative Example 1, and the piezoelectric elastomer film prepared in Example 2.
[0035] Figure 2 This is a microscope image of the piezoelectric elastomer film prepared in Example 2.
[0036] Figure 3 These are actual images of the piezoelectric elastomer film prepared in Example 2 in different states.
[0037] Figure 41 is a stress-strain curve diagram of the films prepared in Examples 1-6 and Comparative Example 1.
[0038] Figure 5 Graph showing the Young's modulus data of the films prepared in Examples 1-6 and Comparative Example 1 when they were broken.
[0039] Figure 6 This is a cyclic stress-strain curve of the piezoelectric elastomer film prepared in Example 2.
[0040] Figure 7 Graph showing the piezoelectric coefficient data of the piezoelectric elastomer films prepared in Examples 1-6.
[0041] Figure 8 This is a data graph of the piezoelectric coefficient of the piezoelectric elastomer film prepared in Example 2 under different strain conditions.
[0042] Fig. 9 Graph showing output voltage data of the piezoelectric elastomer films prepared in Examples 1-6.
[0043] Fig.10 Graph showing output current data of the piezoelectric elastomer films prepared in Examples 1-6.
[0044] Fig.11 This is a graph showing the output voltage data of the piezoelectric elastomer film prepared in Example 2 after 4000 continuous impact cycles.
[0045] Fig.12 Confocal images of the activity and proliferation of mouse preosteoblasts on the films prepared in the blank group, comparative example 1 and example 2.
[0046] Fig.13 Confocal images of the activity and proliferation of mouse fibroblasts on the films prepared in the blank group, comparative example 1 and example 2.
[0047] Fig.14 The bioactivity data of mouse preosteoblasts detected by CCK-8 method (24 h) at different concentrations.
[0048] Fig.15 The biological activity data of mouse fibroblasts detected by CCK-8 method (24 h) at different concentrations. DETAILED DESCRIPTION
[0049] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0050] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0051] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0052] In a first aspect, the present invention provides a piezoelectric elastomer material, comprising piezoelectric molecular crystals and a polymer elastic matrix, wherein the polymer elastic matrix forms an elastic skeleton of a three-dimensional network structure, the piezoelectric molecular crystals are connected to the three-dimensional network structure of the polymer elastic matrix through hydrogen bonds and filled in the pores of the elastic skeleton, the components of the piezoelectric molecular crystals include hexafluoropentanediol or dodecafluorononanediol, the components of the polymer elastic matrix are degradable elastic polymers, the degradable elastic polymers include degradable waterborne polyurethane polymers or degradable polyester polymers, and the mass ratio of the piezoelectric molecular crystals to the polymer elastic matrix is (0.2-3):1.
[0053] The piezoelectric elastomer material provided by the present invention adopts molecular crystals formed by crystallization of small molecule hexafluoropentanediol or dodecafluorononanediol as piezoelectric molecular crystals providing piezoelectric effect. The piezoelectric molecular crystals have an ordered two-dimensional hydrogen bond network and asymmetrically distributed F atoms, which work together to enable the piezoelectric elastomer material to have a high piezoelectric coefficient without polarization. A degradable waterborne polyurethane polymer or a degradable polyester polymer with excellent elasticity is adopted as an elastic matrix to form a polymer network structure consisting of alternating soft segments and hard segments, thereby providing elasticity and flexibility. Both ends of the molecules of the hexafluoropentanediol or dodecafluorononanediol adopted have hydroxyl groups, and have a high bonding ability with the degradable waterborne polyurethane polymer or the degradable polyester polymer. The ratio of the piezoelectric molecular crystals to the polymer elastic matrix is further optimized. The piezoelectric molecular crystals and the polymer elastic matrix cooperate with each other to enable the piezoelectric elastomer material to have both good elasticity and good toughness. The piezoelectric elastomer material has good elasticity, flexibility, and appropriate strength and hardness; and the piezoelectric molecular crystals and polymer elastic matrix used in the piezoelectric elastomer material have good biocompatibility, ensuring the overall biocompatibility of the piezoelectric elastomer material; moreover, the water-based polyurethane polymer or polyester polymer used in the piezoelectric elastomer material is also degradable, and the piezoelectric molecular crystals used can be excreted from the body through the biological metabolic system, avoiding secondary damage to the organism due to the need to remove the piezoelectric material from the organism; under the mutual synergistic effect of the piezoelectric molecular crystals and the polymer elastic matrix, the piezoelectric elastomer material of the present invention presents a piezoelectric coefficient change trend that is different from the conventional one. Under normal circumstances, the piezoelectric coefficient of the conventional piezoelectric elastomer material decreases with the increase of strain, while the piezoelectric coefficient of the piezoelectric elastomer material in the present invention increases continuously with the increase of strain within the tensile strain range of 0-40%. The piezoelectric molecular crystals and polymer elastic matrix used in the present invention cooperate with each other, so that the piezoelectric elastomer material has suitable strength and hardness, good elasticity and flexibility, high piezoelectric coefficient, excellent biocompatibility, safe degradability or can be excreted from the body through the biological metabolic system.
[0054] Further preferably, the mass ratio of the piezoelectric molecular crystal to the polymer elastic matrix is (1-2): 1. When the mass ratio of the piezoelectric molecular crystal to the polymer elastic matrix is within the range of (1-2): 1, the piezoelectric properties, tensile properties and flexibility of the piezoelectric elastomer material can be optimally balanced. A too low ratio reduces the piezoelectric properties of the piezoelectric elastomer material, and a too high ratio is prone to produce stress concentration areas in the piezoelectric elastomer material, affecting the tensile strength and flexibility of the piezoelectric elastomer material.
[0055] In a possible implementation, the soft segment of the degradable waterborne polyurethane polymer includes at least one of polyether and polyester. The use of the degradable waterborne polyurethane polymer having a soft segment including at least one of polyether and polyester can make the piezoelectric elastic matrix have higher flexibility.
[0056] In a possible embodiment, the degradable polyester polymer includes at least one of a random copolyester of ethylene glycol-cyclohexanedimethanol-succinic acid and a random copolyester of ethylene glycol-cyclohexanedimethanol-furandicarboxylic acid. By using at least one of the random copolyester of ethylene glycol-cyclohexanedimethanol-succinic acid and a random copolyester of ethylene glycol-cyclohexanedimethanol-furandicarboxylic acid, the piezoelectric elastic matrix can have strength, hardness and flexibility that are more compatible with human skin.
[0057] In a possible implementation, the piezoelectric coefficient of the piezoelectric elastomer material is greater than 1 pC / N.
[0058] In a possible implementation, the elastic modulus of the piezoelectric elastomer material is 0.5-50 Mpa.
[0059] More preferably, the mass ratio of the piezoelectric molecular crystal to the polymer elastic matrix is (1-1.5): 1. When the mass ratio of the piezoelectric molecular crystal to the polymer elastic matrix is within the range of (1-1.5): 1, the piezoelectric elastic material has strength, hardness and flexibility that are more compatible with human skin.
[0060] Furthermore, the piezoelectric coefficient of the piezoelectric elastic material is greater than 18 pC / N. When the piezoelectric coefficient of the piezoelectric elastic material is greater than 18 pC / N, the piezoelectric elastic material can respond to the effect of pressure more sensitively.
[0061] Furthermore, the elastic modulus of the piezoelectric elastomer material is 2.5-7 Mpa. When the elastic modulus of the piezoelectric elastomer material is 2.5-7 Mpa, the piezoelectric elastomer material can better match the human skin tissue.
[0062] In a possible implementation, the length of the piezoelectric molecular crystal is 0.2-80 μm. When the length of the piezoelectric molecular crystal is within the range of 0.2-80 μm, the piezoelectric molecular crystal can be more evenly filled in the pores of the elastic skeleton.
[0063] In a second aspect, the present invention further provides a method for preparing the above-mentioned piezoelectric elastomer material, comprising the following steps: S1. A solution of piezoelectric molecules is blended with a solution of a degradable elastic polymer to form a mixed solution, wherein the piezoelectric molecules include hexafluoropentanediol or dodecafluorononanediol, and the degradable elastic polymer includes a degradable waterborne polyurethane polymer or a degradable polyester polymer; in the mixed solution, the mass ratio of the piezoelectric molecules to the degradable elastic polymer is (0.2-3):1; S2. The mixed solution in step S1 is subjected to solvent volatilization, crystal growth and drying treatment, so that the degradable elastic polymer forms a polymer elastic matrix, and at the same time, piezoelectric molecular crystals grow spontaneously inside the polymer elastic matrix to obtain a piezoelectric elastic material.
[0064] The method for preparing a piezoelectric elastomer material provided by the present invention comprises the following steps: firstly blending a solution of piezoelectric molecules and a solution of a degradable elastic polymer to form a mixed solution, and then drying the solution to evaporate the solvent, so that the degradable elastic polymer forms an elastic skeleton with a three-dimensional network structure, and the piezoelectric molecules grow spontaneously inside the elastic skeleton to form piezoelectric molecular crystals tightly bound inside the elastic skeleton. The method for preparing a piezoelectric elastomer provided by the present invention does not require the use of toxic organic solvents, so that the prepared piezoelectric elastomer is safer; the piezoelectric molecular crystals are formed during the molding process of the polymer elastic matrix, so that a strong intermolecular interaction is generated between the piezoelectric molecular crystals and the polymer elastic matrix, and at the same time, the defects inside the piezoelectric elastomer material are minimized, which is beneficial to improving the mechanical properties and piezoelectric properties of the piezoelectric elastomer material; without the need for polarization, a piezoelectric elastomer material with excellent piezoelectric properties is prepared.
[0065] In a possible implementation, the solvent of the solution of piezoelectric molecules and the solution of degradable elastic polymer in step S1 includes at least one of water, ethanol, chloroform and ethyl acetate.
[0066] In a possible implementation, the mass volume ratio of the piezoelectric molecules to the solvent in the solution of the piezoelectric molecules in step S1 is 10-600 mg / mL.
[0067] In a possible implementation, the mass volume ratio of the degradable elastic polymer to the solvent in the solution of the degradable elastic polymer in step S1 is 100-600 mg / mL.
[0068] The thickness of the prepared piezoelectric elastomer material can be controlled by controlling the mass volume ratio of the piezoelectric molecules to the solvent and the mass volume ratio of the degradable elastic polymer to the solvent.
[0069] In a possible implementation, the process of preparing the solution of piezoelectric molecules in step S1 is that the piezoelectric molecules are dissolved in a solvent at a temperature of 10-60° C. and a time of 5-60 min.
[0070] In a possible implementation, the preparation process of the solution of the degradable elastic polymer in step S1 is that the degradable elastic polymer is dissolved in a solvent at a temperature of 10-60° C. and a time of more than 1 min.
[0071] In a possible implementation, the blending temperature in step S1 is 10-40° C. By controlling the blending temperature, the mixed solution system is kept in a flowing state and the molecular crystals are not precipitated, so that the piezoelectric molecules are retained in the mixed solution.
[0072] In a possible implementation, the blending time in step S1 is 10-60 min. By controlling the blending time, the piezoelectric molecules and the degradable elastic polymer can be uniformly mixed to avoid prolonging the preparation time of the piezoelectric elastomer material due to too long a blending time.
[0073] In a possible implementation, the temperature at which the solvent evaporates in step S2 is 30-40° C. By controlling the temperature at which the solvent evaporates, the solvent can be controlled to evaporate at a suitable speed and the piezoelectric molecules can be retained inside the piezoelectric elastic material.
[0074] In a possible embodiment, the solvent volatilization time in step S2 is 6-12 hours. By controlling the solvent volatilization time, it is ensured that most of the solvent is volatilized from the mixed solution and no solvent residue is visible to the naked eye, while also avoiding a long preparation time due to a long volatilization time.
[0075] In a possible implementation, the temperature of crystal growth in step S2 is 10-60° C. By controlling the temperature of crystal growth, the piezoelectric molecules can be controlled to grow at a suitable speed in the elastic skeleton and sublimation of part of the piezoelectric molecule crystals due to excessively high temperature can be avoided.
[0076] In a possible implementation, the crystal growth time in step S2 is 2-6 hours. By controlling the crystal growth time, on the one hand, the length of the piezoelectric molecular crystal can be controlled, and on the other hand, the piezoelectric molecular crystal can be ensured to be evenly dispersed inside the piezoelectric elastomer material and cover the entire piezoelectric elastomer material.
[0077] In a possible implementation, the drying temperature in step S2 is 20-60°C and the drying time is 12-36 hours. By controlling the drying temperature and time, the residual solvent is further removed, which is beneficial to improving the electrical and mechanical properties of the piezoelectric elastomer material, while also avoiding the sublimation of some piezoelectric molecular crystals due to excessively high temperature.
[0078] In a third aspect, the present invention also provides applications of the above-mentioned piezoelectric elastomer material in the fields of biomedicine, wearable devices or piezoelectric generators.
[0079] The technical scheme of the present invention is further described below in conjunction with specific examples. All reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment. The instruments used in the examples are commercially available.
[0080] Example 1 This embodiment provides a piezoelectric elastic film, which is prepared by the following preparation method: S1. Add 150 mg of hexafluoropentanediol (HFPD) to 1.5 mL of water and shake to dissolve for 10 min to obtain a piezoelectric phase solution. S2, 105 g of waterborne polyurethane MR-873A (WPU) was added into 195 mL of water and dissolved to form a polyurethane suspension; S3, the piezoelectric phase solution in step S1 and the polyurethane suspension in step S2 are mixed by shaking at 25° C. for 30 min to obtain a piezoelectric precursor solution; S4. The piezoelectric precursor solution in step S3 is cast on a 2.5 cm×3.8 cm glass slide, and the glass slide is placed on a 40°C heating table for drying for 8 h, and then ventilated and dried for 30 h at 25°C to prepare a piezoelectric elastomer film (HFPD / WPU) with a piezoelectric phase to polymer mass ratio of 0.5:1.
[0081] Example 2
[0082] This embodiment provides a piezoelectric elastic film, which is prepared by the following preparation method: S1. Add 300 mg of hexafluoropentanediol to 1.5 mL of water and shake to dissolve for 10 min to obtain a piezoelectric phase solution; S2, 105 g of waterborne polyurethane MR-873A was added into 195 mL of water and dissolved to form a polyurethane suspension; S3, the piezoelectric phase solution in step S1 and the polyurethane suspension in step S2 are mixed by shaking at 25° C. for 30 min to obtain a piezoelectric precursor solution; S4. The piezoelectric precursor solution in step S3 is cast on a 2.5 cm×3.8 cm glass slide, and the glass slide is placed on a 40°C heating table for drying for 8 h, and then ventilated and dried at 25°C for 30 h to prepare a piezoelectric elastomer film with a piezoelectric phase to polymer mass ratio of 1:1.
[0083] Example 3
[0084] This embodiment provides a piezoelectric elastic film, which is prepared by the following preparation method: S1. Add 375 mg of hexafluoropentanediol to 1.5 mL of water and shake to dissolve for 10 min to obtain a piezoelectric phase solution; S2, 105 g of waterborne polyurethane MR-873A was added into 195 mL of water and dissolved to form a polyurethane suspension; S3, the piezoelectric phase solution in step S1 and the polyurethane suspension in step S2 are mixed by shaking at 25° C. for 30 min to obtain a piezoelectric precursor solution; S4. The piezoelectric precursor solution in step S3 is cast on a 2.5 cm×3.8 cm glass slide, and the glass slide is placed on a 40°C heating table for drying for 8 h, and then ventilated and dried at 25°C for 30 h to prepare a piezoelectric elastomer film with a piezoelectric phase to polymer mass ratio of 1.25:1.
[0085] Example 4
[0086] This embodiment provides a piezoelectric elastic film, which is prepared by the following preparation method: S1. Add 450 mg of hexafluoropentanediol to 1.5 mL of water and shake to dissolve for 10 min to obtain a piezoelectric phase solution. S2, 105 g of waterborne polyurethane MR-873A was added into 195 mL of water and dissolved to form a polyurethane suspension; S3, the piezoelectric phase solution in step S1 and the polyurethane suspension in step S2 are mixed by shaking at 25° C. for 30 min to obtain a piezoelectric precursor solution; S4. The piezoelectric precursor solution in step S3 is cast on a 2.5 cm×3.8 cm glass slide, and the glass slide is placed on a 40°C heating table for drying for 8 h, and then ventilated and dried at 25°C for 30 h to prepare a piezoelectric elastomer film with a piezoelectric phase to polymer mass ratio of 1.5:1.
[0087] Example 5
[0088] This embodiment provides a piezoelectric elastic film, which is prepared by the following preparation method: S1. Add 525 mg of hexafluoropentanediol to 1.5 mL of water and shake to dissolve for 10 min to obtain a piezoelectric phase solution; S2, 105 g of waterborne polyurethane MR-873A was added into 195 mL of water and dissolved to form a polyurethane suspension; S3, the piezoelectric phase solution in step S1 and the polyurethane suspension in step S2 are mixed by shaking at 25° C. for 30 min to obtain a piezoelectric precursor solution; S4. The piezoelectric precursor solution in step S3 is cast on a 2.5 cm×3.8 cm glass slide, and the glass slide is placed on a 40°C heating table for drying for 8 h, and then ventilated and dried for 30 h at 25°C to prepare a piezoelectric elastomer film with a piezoelectric phase to polymer mass ratio of 1.75:1.
[0089] Example 6
[0090] This embodiment provides a piezoelectric elastic film, which is prepared by the following preparation method: S1. Add 600 mg of hexafluoropentanediol to 1.5 mL of water and shake to dissolve for 10 min to obtain a piezoelectric phase solution; S2, 105 g of waterborne polyurethane MR-873A was added into 195 mL of water and dissolved to form a polyurethane suspension; S3, the piezoelectric phase solution in step S1 and the polyurethane suspension in step S2 are mixed by shaking at 25° C. for 30 min to obtain a piezoelectric precursor solution; S4. The piezoelectric precursor solution in step S3 is cast on a 2.5 cm×3.8 cm glass slide, and the glass slide is placed on a 40°C heating table for drying for 8 h, and then ventilated and dried for 30 h at 25°C to prepare a piezoelectric elastomer film with a piezoelectric phase to polymer mass ratio of 2:1.
[0091] Example 7
[0092] This embodiment provides a piezoelectric elastic film, which is prepared by the following preparation method: S1, add 100 mg dodecafluorononanediol to 0.5 mL 2-butanone, shake and dissolve for 10 min to obtain the piezoelectric phase solution; S2, 200 g of random copolyester of ethylene glycol-cyclohexanedimethanol-succinic acid was added into 2 mL of 2-butanone and dissolved to form a random copolyester solution of ethylene glycol-cyclohexanedimethanol-succinic acid; S3, mixing the piezoelectric phase solution in step S1 and the random copolyester solution of ethylene glycol-cyclohexanedimethanol-succinic acid in step S2 at 25° C. for 30 min to obtain a piezoelectric precursor solution; S4. The piezoelectric precursor solution in step S3 is cast on a 2.5 cm×3.8 cm glass slide, placed in a 25°C environment for ventilation and drying for 48 h to prepare a piezoelectric elastomer film with a piezoelectric phase to polymer mass ratio of 2:1.
[0093] Comparative Example 1 This comparative example provides a polyurethane elastomer film, which is prepared by the following preparation method: S1, 105 g of waterborne polyurethane MR-873A was added into 195 mL of water and dissolved to form a polyurethane suspension; S2. The polyurethane suspension in step S1 is cast on a 2.5 cm×3.8 cm glass slide, and the glass slide is placed on a 40°C heating table for drying for 8 h, and then ventilated and dried at 25°C for 30 h to prepare a polyurethane elastomer film.
[0094] The piezoelectric elastomer films prepared in Examples 1-7 and Comparative Example 1 were subjected to the following tests.
[0095] Preparation of HFPD / WPU piezoelectric devices: Aluminum electrode (1×1cm 2) were pasted on both sides of the prepared piezoelectric elastomer film and then encapsulated with polyimide (PI) tape. The encapsulated device was subjected to a pressure of 5 kg for 10 min.
[0096] XRD test: The XRD powder diffractometer (XRD, Germany) was used to scatter the 2 θ The scanning rate is 4° / min.
[0097] Microscope images: A metal mirror (NX30T-3M180, Shenzhen AOSVI Optical Instrument Co., Ltd.) was used to observe the crystal phase distribution of the piezoelectric elastomer film.
[0098] Mechanical properties test: The mechanical properties of the piezoelectric elastomer film were evaluated using an inston-5943 tensile tester with a test rate / speed set to 1 mm / mm / min. During the experiment, the sample was cut into strips with a width of 4 mm.
[0099] Electrical performance test: The relative dielectric constant is ε r The test was carried out on the DMS 2000 (BALAB) platform, and the dielectric loss factor ( Tanδ ).
[0100] Piezoelectric performance test: The piezoelectric coefficient data of the piezoelectric elastic film were collected using aZJ-6AN quasi-static measuring instrument.
[0101] Piezoelectric output characteristics analysis test: To characterize the piezoelectric output performance of the HFPD / WPU film, a linear motor was used to apply different forces at different frequencies. The input force was accurately monitored using an SBT951-T force sensor, and the piezoelectric output voltage and current were recorded using a Keith 6514 ammeter.
[0102] Cytotoxicity assay: Spontaneously immortalized mouse calvarial cell line MC3T3-E1 and mouse fibroblast cell line L929 were cultured in complete medium at 37 °C and saturated humidity with 5% CO. After 24 h of culture, the mouse calvarial cell line MC3T3-E1 and mouse fibroblast cell line L929 were in the logarithmic growth phase and were cultured at a rate of 5×10 3The cells were transferred to a 96-well plate at a density of 1 cell / well and then cultured in a controlled environment of an incubator. The piezoelectric elastomer film solution in each embodiment and comparative example 1 was diluted to a concentration of 1, 5 and 10 µg / mL and added to 96-well plates containing MC3T3-E1 and L929 cells, respectively. After 24 h, the original culture medium was carefully aspirated from the 96-well plate and each well was washed twice with phosphate buffered saline (PBS). Then, 100 μL of the diluted CCK-8 solution was added to each well. After incubation for 2 h, the optical density (OD) was measured at 450 nm using the MK-3 enzyme-linked immunosorbent assay. The method for calculating cell activity is as follows: V =( OD e - OD o ) / ( OD c - OD o ) OD e Represents the optical density value of the experimental group. OD o Represents the optical density value of the blank group. OD c Represents the optical density value of the control group.
[0103] For live / dead staining, 1 μL of Calcein-AM solution and 3 μL of 1.5 mM propidium iodide (PI) solution were mixed into 1 mL of detection buffer to prepare the staining working solution. After the cells were incubated for 24 h under the same conditions as above, the medium was carefully aspirated and discarded, and the cells were washed three times with detection buffer. Then, the staining working solution was added, incubated in the dark at 37 °C for 15 min, and then washed twice with PBS. Live / dead staining images were captured using an M52 inverted fluorescence microscope.
[0104] Test results description: Figure 1 The X-ray diffraction test spectra of hexafluoropentanediol powder, the waterborne polyurethane film prepared in Comparative Example 1, and the piezoelectric elastomer film prepared in Example 2 are shown in the figure. The horizontal axis represents the scanning angle 2 θ (degrees), and the ordinate represents the diffraction peak intensity. As can be seen from the figure, the piezoelectric elastomer film prepared in Example 2 has an obvious diffraction peak at 19.1°, corresponding to the (012) plane of the hexafluoropentanediol crystal, indicating that hexafluoropentanediol has successfully crystallized in the piezoelectric elastomer film. In addition, there is a broad peak near 20°, which is attributed to amorphous diffraction, indicating the presence of waterborne polyurethane.
[0105] Figure 2is a microscope image of the piezoelectric elastomer film prepared in Example 2. As can be seen from the figure, the length of the hexafluoropentanediol crystals is about 1-40 μm, and they are evenly distributed in the piezoelectric elastomer film.
[0106] Figure 3 The figures are real images of the piezoelectric elastomer film prepared in Example 2 in different states. The figures correspond to the flat, bent, twisted, before stretching, during stretching and after stretching states of the piezoelectric elastomer film from top to bottom and from left to right. It can be seen from the figures that the piezoelectric elastomer film prepared in Example 2 can be bent and twisted arbitrarily, showing good stretching properties.
[0107] Figure 4 The stress-strain curves of the films prepared in Examples 1-6 and Comparative Example 1 are shown in the figure, where the horizontal axis represents the tensile strain and the vertical axis represents the tensile stress. As can be seen from the figure, the stress-strain curve of the waterborne polyurethane film prepared in Comparative Example 1 shows its unique elastic behavior, with an elongation of about 400% at break and no obvious yield point. However, the yield phenomenon of the piezoelectric elastomer film prepared in Examples 1-6 becomes more obvious as the content of hexafluoropentanediol crystals increases. When the ratio of hexafluoropentanediol crystals to waterborne polyurethane is 1:1, the uniform distribution of hexafluoropentanediol crystals enhances the contact and adhesion of the crystal-polyurethane interface, reduces the formation of pores during the stretching process, and forms a relatively smooth stress curve.
[0108] Figure 5 The Young's modulus data diagram of the film prepared in Examples 1-6 and Comparative Example 1 when it breaks, the abscissa represents the film samples with different preparation ratios, and the ordinate represents the elastic modulus. Studies have shown that the elastic modulus of human skin is between 0.01-10MPa. When the elastic modulus of the piezoelectric elastomer is within a range close to the elastic modulus of human skin, the comfort of wearing the piezoelectric elastomer can be enhanced. Due to the inherent rigidity of hexafluoropentanediol crystals, when the ratio of hexafluoropentanediol crystals to aqueous polyurethane reaches 1.75, the Young's modulus of the piezoelectric elastomer increases significantly, exceeding 20 MPa. Therefore, keeping the ratio of hexafluoropentanediol crystals to aqueous polyurethane between 1 and 1.5 can make the piezoelectric elastomer film achieve the best balance between stretchability and Young's modulus.
[0109] Figure 6 The cyclic stress-strain curve of the piezoelectric elastomer film prepared in Example 2, the horizontal axis represents the tensile strain, and the vertical axis represents the tensile stress. Since the human body will cause deformation of human tissue during exercise, it is required that the material used in the wearable device has an elastic recovery of at least 50% strain. Figure 6 It can be seen that the piezoelectric elastomer film prepared in Example 2 exhibits higher elastic recovery when subjected to a stretching cycle test.
[0110] Figure 7 The piezoelectric coefficient data of the piezoelectric elastic film prepared in Examples 1-6, the horizontal axis represents the film samples with different preparation ratios, and the vertical axis represents the piezoelectric coefficient ( d 33 ). As can be seen from the figure, when the ratio of hexafluoropentanediol crystal to waterborne polyurethane is 1:1 and 2:1 respectively, the prepared piezoelectric elastomer exhibits an increased piezoelectric coefficient ( d 33 )value.
[0111] Figure 8 The experimental data and fitting line data of the piezoelectric coefficient of the piezoelectric elastic film prepared in Example 2 under different strain conditions, the horizontal axis represents the tensile strain, and the vertical axis represents the piezoelectric coefficient ( d 33 ). As can be seen from the figure, when the tensile strain increases from 0 to 40%, the piezoelectric coefficient of the piezoelectric elastic film gradually increases and has a strong correlation (R 2 =0.99), which may be due to the reduced thickness of the elastic matrix around the hexafluoropentanediol crystals, which improves the stress and charge transport efficiency. When the strain exceeds 40%, the piezoelectric coefficient d 33 The value decreases over a wide strain range up to 200% and stabilizes at approximately 10 pC / N, which is sufficient to meet the strain requirements of skin tissue in daily activities.
[0112] Fig. 9 The output voltage data graph of the piezoelectric elastic film prepared in Example 1-6, the abscissa represents time, and the ordinate represents voltage; Fig.10 The output current data graph of the piezoelectric elastomer film prepared in Example 1-6, the horizontal axis represents time, and the vertical axis represents current. It can be seen from the figure that as the HFPD:WPU ratio increases from 0.5:1 to 1:1, the output voltage and current increase significantly, from 0.049 V to 0.855 V and 0.026 μA to 0.528 μA, respectively. However, as the HFPD content further increases, the output voltage begins to decrease, which may be due to the combined effects of dielectric loss and interface polarization. In addition, the increase in the proportion of piezoelectric molecular crystals reduces the adhesion between the piezoelectric film and the aluminum electrode, resulting in insufficient contact, which hinders the transfer and accumulation of charge; under specific test conditions, when the HFPD:WPU ratio is 1:1, the piezoelectric elastomer film has the best output voltage performance.
[0113] The electrical performance parameters of the films obtained in Examples 1-6 and Comparative Example 1 are shown in Table 1. ε r and d 33Under the synergistic effect of the ratio of 1:1, the piezoelectric voltage coefficient ( g 33 ) reached 361.47 Vm / N.
[0114] Table 1 Electrical performance parameters of the films obtained in Examples 1-6 and Comparative Example 1
[0115]
[0116] Fig.11 The output voltage data of the piezoelectric elastomer film prepared in Example 2 after 4000 continuous impact cycles is shown in the figure. The horizontal axis represents the number of impact cycles and the vertical axis represents the output voltage. As can be seen from the figure, the output voltage increases slightly with the increase in the number of impact cycles. This may be due to the enhanced bonding between the HFPD crystal and the WPU interface under the action of external force, which improves the stress transfer efficiency. It is worth noting that the shape of the response peak of 4000 continuous impact cycles remains basically unchanged, indicating the excellent durability of the piezoelectric elastomer film.
[0117] Fig.12 Confocal images of the activity and proliferation of mouse preosteoblasts on the films prepared in the blank group, comparative example 1 and example 2 (scale bar is 200 μm), Fig.13 The confocal images (scale bar is 200 µm) of the activity and proliferation of mouse fibroblasts on the films prepared in the blank group, comparative example 1 and example 2; green fluorescence shows live cell images, red fluorescence shows dead cell images, and a column of images marked as fusion represents images containing information from two color channels, green fluorescence and red fluorescence. As can be seen from the figure, mouse preosteoblasts and mouse fibroblasts show the formation of filopodia, which further proves their active state and illustrates that the piezoelectric elastic film is non-cytotoxic.
[0118] Fig.14 The data of bioactivity of mouse preosteoblasts detected by CCK-8 method (24 h) at different concentrations are shown in Table 1. Fig.15 The bioactivity data of mouse fibroblasts of different concentrations detected by CCK-8 method (24 h), the abscissa represents the concentration of piezoelectric elastomer film, and the ordinate represents cell activity. As can be seen from the figure, the piezoelectric elastomer film prepared in Example 2 has significant biocompatibility with mouse preosteoblast cells (MC3TS-E1) and mouse fibroblasts (L929), and even if the concentration of the piezoelectric elastomer film is as high as 10 mg / ml, the cell viability is still maintained above 92%. In addition, the water solubility of HFPD promotes its rapid dissolution and excretion through the metabolic process in the body.
[0119] The above test data indicate that the piezoelectric elastomer provided by the present invention meets the basic requirements of biocompatibility and biodegradability, and has great application potential in the biomedical field.
[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A piezoelectric elastic material, characterized in that: The invention comprises piezoelectric molecular crystals and a polymer elastic matrix, wherein the polymer elastic matrix forms an elastic skeleton of a three-dimensional network structure, the piezoelectric molecular crystals are connected to the three-dimensional network structure of the polymer elastic matrix through hydrogen bonds and are filled in the pores of the elastic skeleton, the components of the piezoelectric molecular crystals include hexafluoropentanediol or dodecafluorononanediol, the components of the polymer elastic matrix are degradable elastic polymers, the degradable elastic polymers include degradable waterborne polyurethane polymers or degradable polyester polymers, and the mass ratio of the piezoelectric molecular crystals to the polymer elastic matrix is (0.2-3):
1.
2. The piezoelectric elastomer material according to claim 1, characterized in that: The mass ratio of the piezoelectric molecular crystal to the polymer elastic matrix is (1-2):1; and / or, the soft segment of the degradable waterborne polyurethane polymer comprises at least one of polyether and polyester; And / or, the degradable polyester polymer comprises at least one of a random copolyester of ethylene glycol-cyclohexanedimethanol-succinic acid and a random copolyester of ethylene glycol-cyclohexanedimethanol-furandicarboxylic acid; and / or, the piezoelectric coefficient of the piezoelectric elastomer material is greater than 1 pC / N; And / or, the elastic modulus of the piezoelectric elastomer material is 0.5-50 Mpa.
3. The piezoelectric elastomer material according to claim 2, characterized in that: The mass ratio of the piezoelectric molecular crystal to the polymer elastic matrix is (1-1.5):1; and / or, the piezoelectric coefficient of the piezoelectric elastomer material is greater than 18 pC / N; And / or, the elastic modulus of the piezoelectric elastomer material is 2.5-7 Mpa.
4. The piezoelectric elastomer material according to claim 1, characterized in that: The length of the piezoelectric molecular crystal is 0.2-80 μm.
5. A method for preparing the piezoelectric elastic material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. A solution of piezoelectric molecules is blended with a solution of a degradable elastic polymer to form a mixed solution, wherein the piezoelectric molecules include hexafluoropentanediol or dodecafluorononanediol, and the degradable elastic polymer includes a degradable waterborne polyurethane polymer or a degradable polyester polymer; in the mixed solution, the mass ratio of the piezoelectric molecules to the degradable elastic polymer is (0.2-3):1; S2. The mixed solution in step S1 is subjected to solvent volatilization, crystal growth and drying treatments, so that the degradable elastic polymer forms a polymer elastic matrix, and piezoelectric molecular crystals grow spontaneously inside the polymer elastic matrix to obtain a piezoelectric elastic material.
6. The method for preparing a piezoelectric elastic material according to claim 5, characterized in that: Step S1: the solvent of the solution of the piezoelectric molecules and the solution of the degradable elastic polymer comprises at least one of water, ethanol, chloroform and ethyl acetate; And / or, the mass volume ratio of the piezoelectric molecules to the solvent in the piezoelectric molecule solution in step S1 is 10-600 mg / mL; And / or, in the solution of the degradable elastic polymer in step S1, the mass volume ratio of the degradable elastic polymer to the solvent is 100-600 mg / mL.
7. The method for preparing a piezoelectric elastic material according to claim 6, characterized in that: Step S1: the piezoelectric molecule solution is prepared by dissolving the piezoelectric molecule in the solvent at a temperature of 10-60° C. and a time of 5-60 min. And / or, in step S1, the preparation process of the solution of the degradable elastic polymer is that the degradable elastic polymer is dissolved in the solvent, and the dissolution temperature is 10-60° C. and the time is greater than 1 min.
8. The method for preparing a piezoelectric elastic material according to claim 5, characterized in that: The blending temperature in step S1 is 10-40°C; And / or, the blending time in step S1 is 10-120 min.
9. The method for preparing a piezoelectric elastic material according to claim 5, characterized in that: The temperature at which the solvent evaporates in step S2 is 30-40°C; And / or, the time for evaporation of the solvent in step S2 is 6-12 h; And / or, the temperature of the crystal growth in step S2 is 10-60°C; And / or, the crystal growth time in step S2 is 2-6 h; And / or, the drying temperature in step S2 is 20-60° C. and the drying time is 12-36 h.
10. Application of the piezoelectric elastomer material according to any one of claims 1 to 4 in the fields of biomedicine, wearable devices or piezoelectric generators.
Citation Information
Patent Citations
Flexible piezoelectric thin film composite and preparing method thereof
CN110272620A
Method for preparing fluorine-containing dihydric alcohol from fluorine-containing cycloolefin
CN113045380A
Piezoelectric powder particulates for additive manufacturing and methods associated therewith
WO2023003814A1
KR20240077150A
Cited By
Self-polarization degradable gradient electroactive hydrogel and preparation method and application thereof
CN122701950A